Drivers of California’s changing wildfires: a state-of-the-knowledge synthesis - MacDonald, Glen; Wall, Tamara; Enquist, Carolyn A. F.; LeRoy, Sarah R.; Bradford, John B.; Breshears, David D.; Brown, Timothy; Cayan, Daniel; Dong, Chunyu; Falk, Donald A.; Fleishman, Erica; Gershunov, Alexander; et al. (International journal of wildland fire, 2023)
Over the past four decades, annual area burned has increased significantly in California and across the western USA. This trend reflects a confluence of intersecting factors that affect wildfire regimes. It is correlated with increasing temperatures and atmospheric vapour pressure deficit. Anthropogenic climate change is the driver behind much of this change, in addition to influencing other climate-related factors, such as compression of the winter wet season. These climatic trends and associated increases in fire activity are projected to continue into the future. Additionally, factors related to the suppression of the Indigenous use of fire, aggressive fire suppression and, in some cases, changes in logging practices or fuel management intensity, collectively have produced large build-ups of vegetative fuels in some ecosystems. Human activities provide the most common ignition source for California’s wildfires. Despite its human toll, fire provides a range of ecological benefits to many California ecosystems. Given the diversity of vegetation types and fire regimes found in the state, addressing California’s wildfire challenges will require multi-faceted and locally targeted responses in terms of fuel management, human-caused ignitions, building regulations and restrictions, integrative urban and ecosystem planning, and collaboration with Tribes to support the reinvigoration of traditional burning regimes.